'Give me the space to live': trauma, casted land and the search for restitution among the Meghwal survivors of the Dangawas massacre. Issue 3 (2nd July 2020) - Fuchs, Sandhya
ABSTRACT: May 2015 witnessed the Dangawas massacre in Rajasthan's Nagaur district, one of the most brutal caste atrocities in recent Indian history, which resulted in the death of five Dalits of the Meghwal caste at the hands of a Jat mob. Across Rajasthan, the violence of Dangawas, which marked the culmination of a decades-long land conflict, has become synonymous with the continuing reality of caste-based violence and the law that is meant to address it: The 1989 SC/ST Prevention of Atrocities Act. However, Meghwal survivors in Dangawas often articulate scepticism about the ability of law to provide them with a true sense of restitution. Emphasising a desire for social space ( jagah ), which they map onto the land at the root of the bloodshed, Dangawas' Meghwal survivors are caught in a post-traumatic moment marked by fear of further suffering. The memory of inconceivable violence, which has left them alienated in a divided village, has not only made renewed attempts of assertion, and demands for radical justice temporarily inconceivable, but has also led Dangawas' survivors to ask questions about their own agency and the meaning of sociality in an environment where members of a dominant caste still see themselves as guarantors of economic and social belonging.